2016
DOI: 10.11604/pamj.2016.24.20.8181
|View full text |Cite
|
Sign up to set email alerts
|

Non alcoholic fatty liver disease in Nigerian population with type II diabetes mellitus

Abstract: IntroductionWorldwide, Non-alcoholic fatty liver disease (NAFLD) has become an important cause of chronic liver disease and cardiovascular morbidity, even more so in subjects with Type II Diabetes Mellitus (T2DM). The aim of this study was to determine the prevalence and risk factors of NAFLD in an African population with Type II Diabetes Mellitus.MethodsWe performed a case control study and evaluated anthropometric and biochemical risk factors for NAFLD in 336 subjects (T2DM and non-diabetic controls). Parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…The data that are available from other populations suggest that the overall prevalence of NAFLD in sub-Saharan Africa is low [ 36 ]. In a case-control study undertaken in Nigeria, 16.7% of patients with type II diabetes mellitus were found to have NAFLD compared with only 1.2% of non-diabetic control subjects, suggesting that, in comparison with Caucasian, Indian and Asian populations, diabetes may be a more important risk factor for NAFLD in Africa than obesity [ 37 ]. None of the patients in the present study was obese; other than one case with alcoholic liver disease, none had significant steatosis on hepatic ultrasound and only one had diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The data that are available from other populations suggest that the overall prevalence of NAFLD in sub-Saharan Africa is low [ 36 ]. In a case-control study undertaken in Nigeria, 16.7% of patients with type II diabetes mellitus were found to have NAFLD compared with only 1.2% of non-diabetic control subjects, suggesting that, in comparison with Caucasian, Indian and Asian populations, diabetes may be a more important risk factor for NAFLD in Africa than obesity [ 37 ]. None of the patients in the present study was obese; other than one case with alcoholic liver disease, none had significant steatosis on hepatic ultrasound and only one had diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, NAFLD preva lence of 9.5-16.7% in individuals with diabetes and 1.2-4.5% in individuals without diabetes has been reported 63,64 . Similarly, in South Africa, the prevalence in individuals who were obese or overweight was 45-50% 65 .…”
Section: Incidence Of Nafld and Future Projections In Europementioning
confidence: 99%
“…27 This probably explains why central obesity as determined by waist circumference was also significantly associated with NAFLD. 26 This study showed that the prevalence of impaired glucose tolerance and type 2 diabetic mellitus was significantly higher in participants with NAFLD when compared to non NAFLD patients. This concurs with finding in the literature.…”
Section: Discussionmentioning
confidence: 69%
“…Obesity is an independent risk factor for NAFLD and it is strongly associated with the progression of the disease. 26 The role of central adiposity seems crucial because visceral fat is an important source of triglycerides leading to steatosis. 27 This probably explains why central obesity as determined by waist circumference was also significantly associated with NAFLD.…”
Section: Discussionmentioning
confidence: 99%